Support of decision-making on economic and social sustainability of public transport - Černý, Jan; Černá, Anna; Linda, Bohdan (Transport, 2014)
The main purpose of the paper is to present theoretical findings suitable as a support of decision-making on economic sustainability and accessibility of public transport. Czech experience with solving this problem is taken into account. The paper focuses on the relationship between two of three pillars of public transport sustainability – social and economic. Accessibility of public transport service for the clients is considered the main feature of the social pillar. Three types of accessibility are taken into account: spatial, time and economic. Indicators of all three types are presented and their role is studied in details. The main factors influencing the indicators are described. It is shown that, usually, strengthening the social pillar is then weakening the economic one. Further, the public transport accessibility issues are discussed in the most complicated case – in the weak demand areas. Demand Responsible Transport (DRT) is presented as an efficient and effective tool in maintaining the public transport sustainable in these areas. Different types of DRT are outlined and evaluated for the purpose of deciding which one to choose.First Published Online: 25 Mar 2014